Secretory Mammary Carcinoma In Situ in a Cat - Possa dos Reys, Marina; Rezende Souza, Fernanda; Almeida Viscone, Érica; Yumi Ribeiro Nakagaki, Karen; Cassali, Geovanni Dantas (Acta Scientiae Veterinariae, 2025)
Background: Secretory carcinoma is a rare mammary neoplasm observed in humans and animals. It was 1st called juvenile carcinoma. Secretory carcinoma is characterized by eosinophilic secretory material, both intra- and extracellularly, and neoplastic cells with a signet ring appearance. It is usually invasive, with a few rare reports of its non-invasive form, secretory carcinoma in situ, in humans. In veterinary medicine, only 2 cases of secretory carcinoma have been reported, both in dogs. This case is the 1st report of secretory carcinoma in a cat and the 1st instance of secretory carcinoma in situ in veterinary medicine, highlighting its histopathological, histochemical and immunohistochemical features. Case: A 15-year-old female mixed-breed cat was presented with multiple small nodules located in the right mammary chain. The cat underwent a mastectomy to remove the affected tissue. Upon histological examination of the cranial abdominal mammary gland (A1), a well-delimited neoplasm was identified. The tumor exhibited tubular and cluster formations of cells, with no evidence of invasion beyond the basal membrane. There was a significant deposition of both inter- and extracellular eosinophilic material, and the neoplastic cells showed prominent vacuolation, giving them a signet ring appearance. To further support the suspected diagnosis of secretory carcinoma, histochemical and immunohistochemical tests were conducted. Histochemical staining using Periodic Acid-Schiff (PAS), both with and without diastase digestion, revealed positive results for the neoplastic cells, indicating the presence of secretory material. Additionally, the cells tested positive for the alpha-lactalbumin antibody, further supporting the diagnosis of secretory carcinoma. The Ki67 proliferation index was measured at 30%, which is considered relatively high, indicating a notable degree of cell proliferation. Furthermore, immunohistochemical analysis confirmed the presence of myoepithelial cells surrounding the tubules and cell clusters, as demonstrated by the positivity for alpha-smooth muscle actin and p63. This confirmed the in situ nature of the neoplasm, as the absence of invasion was confirmed, leading to the definitive diagnosis of secretory carcinoma in situ. Unfortunately, no follow-up information was available regarding the cat’s post-surgical condition. Discussion: The diagnosis of secretory mammary carcinoma in animals can be made based on the characteristic morphology, which includes the presence of both intra- and extracellular eosinophilic secretion and the vacuolated, signet ring appearance of the neoplastic cells. Histochemical and immunohistochemical techniques are essential to confirm the diagnosis. PAS staining, with and without the diastase reaction, is useful in identifying the secretory material within the cells. Furthermore, the positivity for alpha-lactalbumin in both the cytoplasm of the neoplastic cells and the extracellular secretion helps corroborate the diagnosis. It is important to differentiate secretory carcinoma in situ from other tumor types with a similar morphology, given the potential for aggressive behavior associated with this neoplasm. However, in the present case, the prognosis is likely more favorable due to the absence of invasion and metastasis, as evidenced by the in situ nature of the tumor. More cases of secretory carcinoma and secretory carcinoma in situ need to be diagnosed and described in veterinary medicine to gain a better understanding of their biological behavior and prognosis. Keywords: feline, alpha-lactalbumin, mammary neoplasm, PAS, secretion.